2017
DOI: 10.1038/s41598-017-02371-2
|View full text |Cite
|
Sign up to set email alerts
|

Odorant-binding proteins expression patterns in recently diverged species of Anastrepha fruit flies

Abstract: We studied two species of closely related South American fruit flies, Anastrepha fraterculus and Anastrepha obliqua which, despite being able to interbreed, still show some ecological and reproductive differences. Because part of these differences, such as host and mate preferences, may be related to olfactory perception, we focused our investigation on the differential expression of Odorant-binding protein (OBP) gene family, which participate in initial steps of the olfactory signal transduction cascade. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 65 publications
4
25
0
1
Order By: Relevance
“…Moreover, we observed slight differences in expression of RferOBP1768 in both sexes (Figure 9 ), and the higher expression level in R. ferrugineus females indicates different roles in pheromone perception for males and females. A similar observation of differential expression patterns of key OBPs in male and female insects has been reported previously (Maida et al, 2005 ; Campanini et al, 2017 ). The differential detection of ferrugineol in males and females associated with distinct sexual behaviors might be because more RferOBP1768 is required in females, leading to differentiation in expression level.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, we observed slight differences in expression of RferOBP1768 in both sexes (Figure 9 ), and the higher expression level in R. ferrugineus females indicates different roles in pheromone perception for males and females. A similar observation of differential expression patterns of key OBPs in male and female insects has been reported previously (Maida et al, 2005 ; Campanini et al, 2017 ). The differential detection of ferrugineol in males and females associated with distinct sexual behaviors might be because more RferOBP1768 is required in females, leading to differentiation in expression level.…”
Section: Discussionsupporting
confidence: 88%
“…In addition to the analysis of these transcripts, the screening of the A. fraterculus transcriptome allowed to identify the presence of other early genes involved in development and sex-determination pathways (transformer, sex-lethal, daughterless, doublesex and slow-as-molasses), all of which showed a low expression level at the stages evaluated in this study. Two of the candidate genes (takeout-like and odorantbinding protein 50a1) involved in courtship [59][60][61] and mate choice [45,[62][63][64][65] in insects, respectively, showed very low expression in embryos and differences in their expression level between males and females of A. fraterculus. Specifically, the transcript annotated as takeoutlike was over-expressed in males relative to females independently of their reproductive status (virgin vs mated individuals).…”
Section: Discussionmentioning
confidence: 99%
“…These volatiles affect the behaviour and physiology of phytophagous insect species and are key components of the mating competitiveness of A. fraterculus males in the field [39][40][41]. Recent studies have utilized a transcriptome approach to identify and differentiate physiological aspects of Anastrepha species [42] and deepen the knowledge of the molecular mechanisms involved in olfaction [43][44][45] and cell processes [46,47].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, odorant-binding proteins (OBPs) are a class of olfactory proteins and are thought to aid in the capture and transport of odorants and pheromones to receptors [80]. In fruit flies, OBP expression levels in females changed significantly after mating [81], and ectopic expression of Obp99b in female fat body tissue led to reduced receptivity and mating success [82]. Our transcriptome data showed that a total of three annotated genes associated with OBPs were downregulated in A. disparis females after mating (table 3; c41154.graph_c0; c29056.graph_c0; c21285.graph_c0), which may explain why mated females become unreceptive to further mating.…”
Section: Discussionmentioning
confidence: 99%